Preparing and Characterizing Porous MgO and NiO/MgO Nano-Compounds - Nguyen Thi Phuong Loan (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2026)
Porous MgO and NiO/MgO nanocomposites have attracted significant attention due to their potential applications in heterogeneous catalysis. In this study, MgO and NiO/MgO nanostructures were successfully synthesized using a modified citrate precursor method. The structural and textural properties of the obtained materials were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and nitrogen adsorption–desorption (BET) analysis. The results reveal that the synthesized MgO exhibits a high specific surface area of up to 230 m²/g with particle sizes ranging from 5 to 20 nm. The incorporation of NiO into the mesoporous MgO matrix leads to changes in pore structure and particle growth behavior. The modified synthesis approach enables improved control over crystallite size and porosity compared to conventional methods. These findings suggest that the prepared materials are promising candidates for catalytic applications.